Unraveling the Pomegranate Genome: Comprehensive Analysis of R2R3-MYB Transcription Factors - Heming Suo; Xuan Zhang; Lei Hu; Huihui Ni; Renzeng Langjia; Fangyu Yuan; Maowen Zhang; Shuiming Zhang (Horticulturae, 2023)
R2R3-MYB TFs represent one of the most extensive gene families in plants and play a crucial role in regulating plant development, metabolite accumulation, and defense responses. Nevertheless, there has been no systematic investigation into the pomegranate R2R3-MYB family. In this study, 186 R2R3-MYB genes were identified from the pomegranate genome and grouped into 34 subgroups based on phylogenetic analysis. Gene structure analysis showed that the PgR2R3-MYB family in the same subgroup had a similar structure. Gene duplication event analysis revealed that the amplification of the PgMYB family was driven by Whole Genome Duplication (WGD) and dispersed duplication. In the upstream promoter sequence of the PgMYB gene, we identified a large number of plant hormones and environmental response elements. Using phylogenetic analysis and RNA-seq analysis, we identified three PgMYB TFs that may be involved in the regulation of lignin synthesis. Their expression patterns were verified by qPCR experiments. This study provides a solid foundation for further studies on the function of the R2R3-MYB gene and the molecular mechanism of lignin synthesis.